Implementation of Authentic Assesment in the Learning of Akidah Akhlak at Madrasah Aliyah Negeri - Hanum, Azizah; Nahar, Syamsu; Tanjung, Adirahman (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The goal of this study was to examine the Authentic Assessment in Akhlak Learning Class IV at Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli and examine the results of authentic assessments in the Akhlak class IV subject at Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli. This thesis research employs a qualitative method with a descriptive approach. The researchers used interview, observation, and document study techniques to collect data, and to strengthen the validity of the data found and the authenticity of the research, they referred to data validity standards such as credibility, transferability, dependability, and confirmability. The findings of this study indicate that authentic assessment of Akidah Akhlak subjects is carried out at Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli at the start of learning, during learning, and after learning. The assessment in learning Akidah Akhlaq is done in an integrated fashion. This assessment is carried out to achieve competence in the 2013 Curriculum, with teaching activities including three assessment aspects: cognitive, affective, and psychomotor. Several assessment techniques are used in the authentic assessment process for Akidah Akhlaq subjects, including written tests, written tests, assignments, practices, projects, portfolios, observations, self-assessments, peer-to-peer assessments, and teacher journals.